A photovoltaic generator system with a DC/DC converter based on an integrated Boost-Ćuk topology. (15th October 2016) - Fernão Pires, V.; Foito, Daniel; Baptista, F.R.B.; Fernando Silva, J.
Highlights: A new non-isolated DC-DC converter with a single switch. Topology characterized by an integration of the classical Boost and Cuk DC-DC converters. Topology that allows extend the voltage static gain when compared with the conventional Boost converter. Semiconductors with reduced voltage stress. Abstract: A new non-isolated DC - DC converter for photovoltaic systems is proposed in this paper. This converter topology is characterized by an integration of the classical Boost and Ćuk DC - DC converters. The proposed topology requires only a single power semiconductor switch, reduces voltage stress across diodes and power semiconductor switch while providing a continuous input current. Further, this topology allows extending the voltage static gain when compared with the conventional Boost converter. The new converter is regulated by a PWM technique at constant frequency that can be associated to a maximum power point tracking algorithm. Herein, the design considerations of this power converter are presented, and the characteristics of the proposed topology are confirmed by simulations and experiment results from a laboratory prototype.